Infrastruktur Perpustakaan Digital dan Preferensi Mahasiswa dalam Mengembangkan Budaya Literasi di Perguruan Tinggi: Studi Kasus di Universitas Negeri Sunan Ampel Surabaya Tahun 2023-2024 - Sutikno Sutikno; Amelia Khoirunisa (Universitas Sebelas Maret Library, 2025)
This research analyzes the preferences of Sunan Ampel Surabaya State Islamic University (UINSA) students towards digital libraries and their influence on literacy culture. Using a qualitative method with a phenomenological approach, this research explores students' experiences in accessing digital libraries. Data were collected through interviews, observations, and document analysis, with purposively selected participants. The results showed that the digital library infrastructure at UINSA is adequate, but still needs improvement in accessibility, content relevance, and ease of use. Students' preferences are influenced by convenience, academic needs, and time efficiency, which have an impact on the intensity of their use. Strengthening the culture of literacy requires synergy between library managers, lecturers, and students through academic literacy programs. This research provides recommendations for optimizing digital libraries in supporting literacy culture in Islamic universities